Pengaruh Modal, Tenaga Kerja Dan Bahan Baku Terhadap Pendapatan Pengusaha Industri Sanggah Di Kecamatan Mengwi - Nayaka, Komang Widya; Kartika, I Nengah (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.07.NO.08.TAHUN 2018, 2018)
As the industrial center, Mengwi District has the opportunity to develop better and more advanced sanggah industry, so that it will affect the high income level. The purpose of this study is to analyze the effect of capital, labor and raw materials simultaneously and partially to the income of industrial entrepreneurs sanggah in District Mengwi.The location of this research is in District Mengwi, Badung regency. The scope of this research is carried out by focusing on the income of the sanggah industrial entrepreneurs and the factors that influence them. The method of determining the sample in this study using the method of Non Probability Sampling. By using the Slovin formula, the population of 132 industrial business entrepreneurs and error limits of 10 percent, then obtained a sample of 57 industrial entrepreneurs.Teknik data analysis used to solve problems in this study is a technique of multiple linear regression analysis.The results showed that capital, labor, and raw materials simultaneously significantly influence the income of industrial entrepreneurs sanggah in District Mengwi. Capital, labor, and raw materials partially have a positive and significant impact on the income of industrial entrepreneurs in Mengwi District. This means that the greater the capital spent, the labor used and the amount of raw materials owned, the greater the likelihood of the number of products produced, so the possibility of income received greater than the proceeds from the sale of production.